1997
DOI: 10.1128/mcb.17.7.3614
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Resolution Analysis of Products of Intrachromosomal Homeologous Recombination in Mammalian Cells

Abstract: Mouse Ltk؊ cell lines that contained a herpes simplex virus type 1 (HSV-1) thymidine kinase (tk) gene with a 16-bp insertion mutation linked to either a defective HSV-2 tk gene or a hybrid tk sequence comprised of HSV-1 and HSV-2 tk sequences were constructed. HSV-1 and HSV-2 tk genes have 81% nucleotide identity and hence are homeologous. Correction of the insertion mutant HSV-1 tk gene via recombination with the hybrid tk sequence required an exchange between homeologous tk sequences, although recombination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 54 publications
3
21
1
Order By: Relevance
“…Strand exchange can penetrate homeologous sequences: In considering how the fastidious exclusion of homeologous sequence from recombination products may be brought about, we bore in mind our earlier studies in which substrates that contained hybrid donors (and were similar to pHYB12-8 and pHYB21A) yielded gene conversion tracts that in some cases included .300 bp of homeologous sequence (Yang and Waldman 1997). The exclusion of homeologous sequence from gene conversion tracts in our current work seemed at odds with those earlier studies.…”
Section: à8contrasting
confidence: 57%
See 2 more Smart Citations
“…Strand exchange can penetrate homeologous sequences: In considering how the fastidious exclusion of homeologous sequence from recombination products may be brought about, we bore in mind our earlier studies in which substrates that contained hybrid donors (and were similar to pHYB12-8 and pHYB21A) yielded gene conversion tracts that in some cases included .300 bp of homeologous sequence (Yang and Waldman 1997). The exclusion of homeologous sequence from gene conversion tracts in our current work seemed at odds with those earlier studies.…”
Section: à8contrasting
confidence: 57%
“…Experiments with pHYB21A-28 in conjunction with our earlier studies (Yang and Waldman 1997;Waldman et al 1999) suggest that certain DNA motifs or sequences might influence recombination. In pHYB21A-28, the XhoI linker in the recipient tk gene is positioned opposite the homeologous portion of the donor when recipient and donor are paired (Figure 1).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…However, the donor loci in this system were not identical, and the focus of the study was on the efficiency of the homology search and whether the search occurs near or far from broken ends. In mammalian cells, HR efficiency is reduced by heterologies (16,79), and this is likely to influence donor preference when potential donors differ in the degree of sequence similarity to a recipient locus. In mouse cells, Tremblay et al (70) showed that DSBs at an I-SceI site within a LINE element were repaired by conversion involving other LINE elements and that the most commonly used donors were those most active in retrotransposition.…”
mentioning
confidence: 99%
“…While diversions exist for every evolved factor among different species, there are some factors which constantly catalyze and assist the associated evolutionary track. Such factors including the Mutation (be it lethal [9] or linked [10][11][12][13]), Genetic Recombination & count of such sites occurring during the crossing-overs [14][15][16][17] and Environmental Constraints form the primary tools to pave the path for evolution. Such factors normally act along with several other key constraints together to demarcate the evolutionary path.…”
Section: Evolutionary Factorsmentioning
confidence: 99%